The UK National Infrastructure Plan 2010 - James Stewart (EIB Papers, 2010)
The challenges of infrastructure finance need to be considered in the context of long-term infrastructure planning. This article outlines the UK's new integrated approach to infrastructure planning to meet large investment needs against the backdrop of fiscal consolidation. The UK National Infrastructure Plan for the first time sets out a broad, integrated, cross-sectoral vision and plan for the substantial infrastructure investment required to underpin the UK's economic growth. This plan will act as a common reference point for the public and private sectors to achieve more effective infrastructure development. It will be updated on an annual basis.
Keywords: 330